Digital Culture Industry - Allen-Robertson, James. author. (orcid)0000-0002-1668-8140 Link aut Link
X, 231 p.
Keywords: How did digital media happen ? Through a unique approach to digital documents, and detailed intricate histories of illicit internet piracy networks, The Digital Culture Industry goes beyond the Napster creation myth and illuminates the unseen individuals, code and events behind the turn to digital media.